Moscoso-Paucarchuco, K. M.; Gutiérrez-Gómez, E. & Fernández-Jaime, R. J. (2023). Prevention of violence against women. Ineffectiveness of law 30364. Huanta - Ayacucho: Fondo Editorial UNAH, 59 pp. - Valverde-Rodriguez, Wilmer Edwin (2023)
This review presents the highlights of the book "Prevención de la violencia contra la mujer. Ineffectiveness of Law 30364" by Moscoso, Gutiérrez & Fernández (2023).